2014
DOI: 10.1252/jcej.13we067
|View full text |Cite
|
Sign up to set email alerts
|

Review of Retrofitting Distillation Columns Using Thermally Coupled Distillation Sequences and Dividing Wall Columns to Improve Energy Efficiency

Abstract: Distillation is a common energy-intensive process. Accordingly, it is the rst process to be addressed to improve the energy e ciency over both the short-and long-term. Recent studies and industrial applications have proven that advanced process integration and process intensi cation techniques such as the use of a thermally coupled distillation sequence (TCDS) and a dividing wall column (DWC) require the lowest amount of energy for the separation of mixtures into pure product streams. This paper reviews some e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 115 publications
(136 reference statements)
0
22
0
Order By: Relevance
“…Distillation columns are widely used in the petrochemical industry. [1][2][3][4] Research on distillation columns contains two aspects: studying the characteristics and designing the operation strategy. The characteristics of a distillation column must be discussed to acquire the relationship among variables and elucidate the nature of important variables through modeling and analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Distillation columns are widely used in the petrochemical industry. [1][2][3][4] Research on distillation columns contains two aspects: studying the characteristics and designing the operation strategy. The characteristics of a distillation column must be discussed to acquire the relationship among variables and elucidate the nature of important variables through modeling and analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…3, the ethylene component of the feed cannot be recovered instantly and circulation and separation alternated. The ethylene component is conserved, as shown in Eqn (4).…”
Section: Calculation Of Energy Consumption Of Circulationmentioning
confidence: 99%
“…Also, more than one such practice is used at the same time (Olujić et al, 2009;Resetarits et al, 2015). For example, in the case of a single distillation column, Lee and Long (2014) mention that the energy integration is adopted in innumerable ways as in the use of heat pumps, feed splitting, side reboiler or a side condenser, changes in operating pressure, and changing the thermal conditions of the feed stream. Industries that use distillation columns have options of either upgrading units already in operation or using a new advanced column.…”
Section: Introductionmentioning
confidence: 99%
“…Due to high energy consumption in the rectification process the problems of energy efficiency of plants have attracted particular attention [6], [7]. There is an eventual necessity for improving the process technology to increase the rectification efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of pressure in the rectification column is usually associated with a required temperature regime [1], [8], [9]. The studies available on the effect of pressure on the efficiency of rectification columns have often been controversial [7], [10], [11]. Previously, it was theoretically shown that the sharpness of fractionation of rectification columns in the process of operation can be substantially improved by increasing their operating pressure [12], [13].…”
Section: Introductionmentioning
confidence: 99%